Kualitas Hidup Terkait Kesehatan Pada Ibu Hamil Pasca Operasi Caesar: Studi Longitudinal - Nuryana, Riska; Elsanti, Devita; Sumarmi, Sumarmi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Research focusing on the quality of life after Caesarean Section (CS) and during subsequent pregnancies is still minimal. In addition, research on the quality of life after multiple CSs is still lacking. Several studies focus on the assessment of the quality of life of pregnant women after giving birth by comparing the type of birth: CS versus vaginal delivery (normal delivery). Objective: This study aims to compare the assessment of health-related quality of life in pregnant women who have a history of CS in the first, second and multiple CSs depending on the number of CSs in the pregnant woman's health history. Methods: A short longitudinal study will be conducted on pregnant women with a history of CS on the day before the planned caesarean section (CS)-T1, and on the third day after CS-T2. Pregnant women with a history of CS are divided into three groups. Group 1: never CS; Group 2: ever CS 1 time; Group 3: ever CS two or more times. Pregnant women will fill out a questionnaire regarding respondent characteristics, obstetric history, surgical or anesthesia history and the health-Related Quality of Life (HRQoL) Questionnaire. General linear model for repeated measurement is used by analyzing correlated and non-independent data that are measured repeatedly. Results: The results of this study showed that GLM with repeated measures was conducted to examine the effect of time (time I, time II and time III) on the quality of life variable. The analysis revealed a significant main effect of time, F (2.39) = 4750.43, p-value = 0.000, indicating that quality of life changed significantly at three time points. Conclusion: An individual approach is needed in planning pregnancy after cesarean, especially to prevent long-term health risks. Education and counseling to help mothers understand the recovery process and manage stress or anxiety. This study provides important insights for health professionals to improve post-cesarean services, both in terms of medical interventions and psychosocial support. Keywords : Sectio Caesarea (CS); quality of life; pregnant women, surgery